How to succeed in small-school headship: a reflection - Johnston, Peter M. (2019)
This thesis is based on a six-year period of my first headship in a small village school. Through my story, I have investigated skills, attributes and knowledge that are required to ‘succeed’ in the endeavour of a small-school headship.